PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN PADA PT.MNC SKY VISION.TBK JAKARTA - Ganjar dan Muhammad Halilintar (Jurnal Manajemen FE-UB, 2017)
The data used in this study are primary data collected through questionnaires and other literature studies. The population in this research is PT.MNC Sky Vision.Tbk customers. Jakarta with a sample of 100 respondents. The data analysis technique used in this research includes validity test, reliability test, classical assumption test, sub structure test I and Sub Structure 2, and path analysis (path analisys), to test and proves the research hypothesis.The results showed that Price and Service Quality Affects Customer Satisfaction. Price has direct effect to Customer Loyalty. Quality of Service directly affects Customer Loyalty. Price and Service Quality affects Customer Loyalty through Customer Satisfaction. Keywords: Price, Service Quality, Customer Satisfaction, Customer Loyalty